DAMPAK MANAJEMEN TALENTA PADA KINERJA ORGANISASI: PERAN MODERASI DARI SISTEM MANAJEMEN KINERJA YANG EFEKTIF - Elia Sjachriatin (Media Mahardhika, 2019)
Despite theoretical and empirical evidence that talent management improves the organization's performance, it remains one of the key challenges facing organizations around the world and particularly in the healthcare sector. This study examines the moderating effects of effective performance management systems as well as the relationship between talent management and organizational performance. This study was conducted in the public health sector and was specifically targeted at public health officials in Bojonegoro. The research focused on 30 public hospitals and health centers in Bojonegoro. The survey of 430 respondents, made up of public health officials, was used for analysis. The study used SEM in the AMOS statistical analysis package. The findings of the study suggest that performance management systems moderating the relationship between talent management and organizational performance show that performance management systems can be used as strategies to identify talented employees; integrating, restructing strategies and strengthening employee-management relationships to improvetheir organization'sperformance.